Making emotions count through CLIL - Adriana Marina Puente; Milena Rojas; Johana Chavelí Corral (Latin American Journal of Content and Language Integrated Learning, 2023)
In this article, we consider the importance of learner well-being for a better performance during the learning process, taking into account their emotions and how they affect them. The CLIL approach is used to integrate learners’ language knowledge and provides strategies about how to manage their emotions and develop a positive mindset. In this context, we suggest three meaningful activities for teenage learners to identify and analyze their emotions while learning and encourage their critical thinking, creativity, and collaborative work. Furthermore, learners can learn about how emotions affect not only their school, but also their personal lives. Through these proposed activities, students may develop some tools and pieces of advice to take care of their emotional health.